Praktikalitas Training Kit Mobile Robotic pada Jurusan Teknik Elektronika Industri - Habibullah, Habibullah; Ambiyar, Ambiyar; Setyawan, Herlin; Risfendra, Risfendra; Sardi, Juli (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2023)
Vocational high schools are schools that provide workers who have knowledge and skills in their respective fields. The Industrial Electronics Engineering Department is a department that provides competent workforce in the field of robotics. Payakumbuh State Vocational School 2 majoring in Industrial Electronics Engineering is experiencing problems implementing robotics learning. The problem is that schools do not yet have robotic training kits that can be used like robots in industry. Schools only have robotic training kits that can be used to understand the basic input and output uses of robots and cannot be used practically with robots in industry. Based on these problems, the aim of this research is to develop a mobile robotic training kit that is practical and can be used from basic learning to learning complex robots such as industrial applications. The research method used in this research is the research and development (R&D) method. So the results obtained in this research are a mobile robotic training kit which is considered very practical by teachers with a percentage of 88.95%. It can be concluded that the mobile robotic training kit is very practical to use in the robotics learning process